Abnormal aortic valve echoes in mitral prolapse. Echocardiographic features of floppy aortic valve. Issue 4 (April 1982) - Rodger, J C; Morley, P
Abstract : The following distinctive combination of M-mode and two dimensional echocardiographic abnormalities of the aortic valve was observed in a group of 12 patients, of whom 11 had mitral valve prolapse. On two dimensional scans, the aortic cusps were freely mobile but appeared thickened or folded. On M-mode records, cusp excursion was normal: there was well defined systolic oscillation, and cusp echoes were multiple and centrally positioned within the aortic root during diastole. The aortic valve was inspected at operation in two patients: a typically myxomatous valve was replaced in one and findings were in keeping with this diagnosis in the other. It is suggested that the echocardiographic features described are characteristic of the floppy aortic valve. Despite the echocardiographic abnormalities, only three patients had clinical evidence of an aortic valve lesion. It is, therefore, further suggested that the investigation of patients with mitral prolapse should include echocardiographic assessment of the aortic valve, even when associated myxomatous degeneration of that valve is not suspected clinically.